Focusing health equality, efficiency and health maximization policy review - Thant Zin; Than Myint; Shamsul Bahari Shamsudin; Wai PW; Htun HN; Osman Ali (Malaysian Public Health Physicians’ Association, 2013)
With economic growth and significant technological advances in the health sector, many countries have developed aggregate outcomes in terms of both health services and individual well-being. Life expectancy has seen a remarkable increase of more than fifty per cent between 1950 and 2009. Achievement is uneven, however, and some groups are better able to access health services than others. In our review, we explore the need and how to maximize health equity, efficiency and effectiveness. Methodology is the review and web surfing on public health, social science, humanity and development literature. The increasing gap in health inequality, however, calls for further reform of the health system to achieve both equity and efficiency. Health is essential for survival and human capability. Good health enables people to participate in society. A new approach to efficient and cost-effective health service provision is community participation in health development. Participation can increase the skills and knowledge of local people, thus providing opportunities to improve their lives (empowerment). Analysis suggests four functional changes to achieve equity and efficiency in maximizing health outputs: reforms targeting universal coverage to achieve universal access to health; people-centred service delivery through concentrating on health services based on need; public policy change targeting integrated and multi-system health planning; and collective health system and community response to achieve health for all.